Drafting "foot soldiers": The social organization of the war for talent. Issue 3 (July 2016) - Porschitz, Emily T; Smircich, Linda; Calás, Marta B
The "global war for talent" refers to the increasing competition among organizations and regional governments for top employees. The concept of "war" in this context acts as a powerful metaphor, heightening the intensity with which organizational and regional leaders mobilize their efforts to create, attract, and retain "top talent." However, this article argues that the "war for talent" is not a distant practice articulated between corporate and state spheres of action but a set of activities directly connected to those in higher education institutions. Framed through the theoretical and methodological approach of Institutional Ethnography, this study tracked students' activities and experiences with a university's economic development initiative, Generation Now, showing how the students' experiences are connected to the global war for talent, how they become its foot soldiers, and with what consequences. More generally, tracing these connections is critical for making sense of contemporary modes of organizing in university classrooms, furthering class hierarchies and neoliberal rationales not necessarily related to students' educational expectations in the conventional sense. Specifically in this case, experiences derived from classroom activities drafted and differentiated students for a war not of their making while naturalizing their "rightful" places in the global economy.